Le traiettorie plurali del corso di vita dei calciatori: note di campo da un’indagine qualitativa su giovani atleti - Pirone, Francesco; Rizzo, Giuseppe (Eracle. Journal of Sport and Social Sciences, 2021)
Being professionally involved in sport could shape on individual’s habits, character, disposition, other than on projects, opportunities and visions. Starting from this, our research focused on how individuals face this pressure, which mostly engage them during the early adolescence. We selected four emblematic cases that could gave us testimony of being involved professionally in football. The research was conducted with a qualitative approach. The empirical material was constructed through direct observation and interviews. As results, we obtained: extensive confirmations of the difficulties experienced by the professionals; the relevance of emotional and socialization aspects and needs; forms of expectations for the future, across efforts of professional conversion, and related obstacles.